(3GdcGajs - (3Gdcdjfj, GdQGRj, GdSdSdj, GdHZOGOj, CHh LYaQ, eMeO Hf jYbhH Hf ESMGb, J (B329 (3g`s
(3ChdgG (B:s
(3Yf GdbGSe Hf eMeO Yf Ydj Hf CHj MeRI bGd SCdfG CHG YHO Gddg Ydjg GdSdGe Yf GdeGA GdSGcf hGdGSJfLGA efg hGdLjaI ajg abGd JhVC ef GdLGfH GdBNQ hdG JhVC ef LGfH GdLjaI (B...s
(3BNQgG (B:s
... (3hde jahV Edjg Cf jRd faSg Cde JQ bhd Gddg YR hLd gGgfG (B{ (3hddg GdYRI hdQShdg hddeDefjf (B} (3hGdeDef jfHZj dg Cf jchf YRHRG hdG jchf PdjdG (B. (3Je cJGH GdLgGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\145s
(3gOjI GdYGQajf (B2\35s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs